Penerapan Jaringan Hotspot Berbasis Mikrotik Menggunakan Metode PPDIO (Prepare, Plan, Design, Implement, Operate, Optimize) - Dimas Fauzi Al Muzaki; Tino Feri Efendi; Muqorobin Muqorobin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Toko Emas Purnama faces challenges in building an efficient, secure, and operationally appropriate internet network infrastructure, particularly to support digital systems such as cloud-based transactions, internal communication, IP Cameras, and hotspot services for customers. This research discusses the implementation of a Mikrotik-based hotspot network at the Purnama Gold Shop area using the PPDIOO (Prepare, Plan, Design, Implement, Operate, and Optimize) method. The objective is to provide a stable, secure, and efficient internet network to support both operational activities and customer needs within the store environment. The PPDIOO methodology is employed as a systematic approach to network planning and deployment, covering the stages from requirement preparation to system performance optimization. The results show that the Mikrotik-based hotspot network offers reliable connectivity with improved bandwidth management and security. Through the PPDIOO method, the network system is developed in a structured and efficient manner, enhancing digital service quality at the Purnama Gold Shop.